(Generalized) B-Fredholm theory relative to a Banach algebra homomorphism - Jamiu, Aliyu (Stellenbosch : Stellenbosch University, 2025)
Jamiu, A. 2025. (Generalized) B-Fredholm theory relative to a Banach algebra homomorphism. Unpublished masters thesis. Stellenbosch: Stellenbosch Univeristy [online]. Available: https://scholar.sun.ac.za/items/2688538a-aa3f-4cac-829b-e8b070491524